(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
This study presents a comprehensive analysis of hazardous solid waste generation and management in residential areas of Hilla City, Iraq, and suggests an innovative pre-treatment method for basis separation. The study found alarming levels of hazardous materials—such as batteries, electronics, medications, paints, and household chemicals—such as around 8.3% of the total waste by carefully compiling and evaluating solid waste from 20 households spread over various neighborhoods in the heart of Hilla city. Every person generated around 1.42 kg of waste daily, with roughly 0.118 kg of possibly dangerous chemicals. This emphasizes how daily behavior adds to environmental dangers. In response, a new three-step separation method was introduced, combining color-coded bins, magnetic sorting for metal hazards and density-based techniques to isolate chemical waste— offering a more practical and effective. During pilot testing, the proposed management system successfully separated hazardous waste with 87% efficiency. If widely adopted, this approach could significantly reduce environmental pollution—by as much as 65%—and greatly enhance the way waste is managed in Hilla City, creating a cleaner and healthier environment for its residents. The study recommends establishment of neighborhood-level hazardous waste collection points and community education programs to ensure sustainable implementation of the proposed system.